2017
DOI: 10.1111/jpi.12378
|View full text |Cite
|
Sign up to set email alerts
|

Novel protective role of the circadian nuclear receptor retinoic acid‐related orphan receptor‐α in diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy is a major complication that significantly contributes to morbidity and mortality in diabetics with few therapies. Moreover, antidiabetic drugs reported inconsistent or even adverse cardiovascular effects, suggesting that it is important to exploit novel therapeutic targets against diabetic cardiomyopathy. Here, we observed that the nuclear melatonin receptor, the retinoic acid-related orphan receptor-α (RORα), was downregulated in diabetic hearts. By utilizing a mouse line with RORα di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 57 publications
(127 reference statements)
4
63
0
Order By: Relevance
“…Similar to the cardioprotective effects of mdivi‐1, we found that melatonin prevented Drp1‐mediated mitochondrial fission and alleviated cardiac dysfunction in diabetic mice. Previous studies have reported that melatonin alleviated cardiac dysfunction via activation of retinoic acid‐related orphan receptor‐α and regulation of autophagy in diabetic hearts . The present work indicates that melatonin‐inhibited mitochondrial fission may be a novel mechanism underlying its cardioprotective effect in diabetes.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Similar to the cardioprotective effects of mdivi‐1, we found that melatonin prevented Drp1‐mediated mitochondrial fission and alleviated cardiac dysfunction in diabetic mice. Previous studies have reported that melatonin alleviated cardiac dysfunction via activation of retinoic acid‐related orphan receptor‐α and regulation of autophagy in diabetic hearts . The present work indicates that melatonin‐inhibited mitochondrial fission may be a novel mechanism underlying its cardioprotective effect in diabetes.…”
Section: Discussionsupporting
confidence: 58%
“…Melatonin was injected at 9:00 am every morning when serum melatonin level was relatively low. The dosage of melatonin or mdivi‐1 treatment was chosen based on previous studies about the effect of melatonin or mdivi‐1 on diabetic complications . At the end of the experiments (12 weeks after the first injection of STZ), hearts were collected for mitochondrial dynamics, apoptosis, ROS generation, and Western blot analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin exerts free radical scavenging and antioxidant actions, thereby protecting against cardiovascular injuries . Accumulating studies indicate that melatonin have protective effects against DCM . Our previous study demonstrated that melatonin alleviated left ventricular remodeling and cardiac dysfunction after myocardial infarction .…”
Section: Introductionmentioning
confidence: 86%
“…Regarding the signaling pathways by which RORα regulates epithelial apoptosis in I/R‐induced AKI, previous studies have reported that the epithelial apoptotic cascade associated with AKI initially comprises mitochondrial deformation, endoplasmic reticulum stress, and the activation of death receptors, followed by the activation of specific caspases and cell death (19). RORα has been demonstrated to suppress myocardial apoptosis by ameliorating mitochondrial dysfunction (mitochondrial swelling) and caspase‐9 activation and down‐regulating endoplasmic reticulum stress markers (11,41). Consistent with these results, our results suggest that the antiapoptotic effects of the RORα pathway in I/R‐induced AKI are associated with the inhibition of mitochondrial and endoplasmic reticulum stress, a phenomenon reflected by decreases in the Bax/Bcl‐2 ratio and the inhibition of caspase‐9 and ‐12 expression.…”
Section: Discussionmentioning
confidence: 99%